Resisting Dispossession : The Odisha Story - Padhi, Ranjana (Springer eBook Collection, 2020)
Chapter 1: Introduction -- Chapter 2: The Disease of Gigantism -- Chapter 3: Recalling Rengali -- Chapter 4: Balco Asura Murdabad -- Chapter 5: The Conch and the Missile -- Chapter 6: Chilika Teere -- Chapter 7: The Kia in Rage -- Chapter 8: The Song of The Mali -- Chapter 9: Juhar Niyamraja -- Chapter 10: The Taste of Steel -- Chapter 11: The Betel Smiles.